Herpes Genitalis: Diagnosis, Treatment and Prevention - Sauerbrei, A. (Geburtshilfe und Frauenheilkunde, 2016)
Herpes genitalis is caused by the herpes simplex virus type 1 or type 2 and can manifest as primary or recurrent infection. It is one of the most common sexually transmitted infections and due to associated physical and psychological morbidity it constitutes a considerable, often underestimated medical problem. In addition to providing the reader with basic knowledge of the pathogen and clinical presentation of herpes genitalis, this review article discusses important aspects of the laboratory diagnostics, antiviral therapy and prophylaxis. The article is aimed at all health-care workers managing patients with herpes genitalis and attempts to improve the often suboptimal counselling, targeted use of laboratory diagnostics, treatment and preventive measures provided to patients.
Keywords: herpes simplex virus; herpes genitalis; laboratory diagnostics; antiviral therapy; prophylaxis